Tidal changes in respiratory resistance are sensitive indicators of airway obstruction in children. Issue 10 (13th May 2016) - Czövek, Dorottya; Shackleton, Claire; Hantos, Zoltán; Taylor, Kate; Kumar, Anushma; Chacko, Archana; Ware, Robert S; Makan, Gergely; Radics, Bence; Gingl, Zoltán; Sly, Peter D
Abstract : Rationale: Individual assessment of airway obstruction in preschool-age children requires sensitive and specific lung function methods with low demand of cooperation. Although the forced oscillation technique (FOT) is feasible in young children, conventional measurements of respiratory impedance (Zrs) have limited diagnostic power in individuals. Objective: To find descriptors of within-breath Zrs that are sensitive indicators of airway obstruction during tidal breathing in children. Methods: Zrs was measured with (i) a standard multifrequency FOT (4–26 Hz) to assess the mean values of resistance and reactance for whole breaths and (ii) a 10 Hz signal to track the within-breath changes. Various Zrs measures obtained in healthy children (n=75) and those with acute wheeze (n=31) were investigated with receiver operator characteristic (ROC) analysis. The cut-off values obtained for airway obstruction were then tested in children with recurrent wheeze (n=20) before and after administration of salbutamol. Results: The largest area under the ROC curve (0.95) was observed for the tidal changes of resistance between the zero-flow values (ΔR). The ΔR cut-off value of 1.42 hPa s/L detected airway obstruction with sensitivity of 92% and specificity of 89% in children with acute wheeze and distinguished children with recurrent wheeze (16/20 above the cut-off value) from healthy children (22/23 below the cut-off value). Furthermore, ΔR significantly decreased after salbutamol in wheezy children but remained unchanged in healthy children. Conclusions: New lung function measure ΔR is able to detect airway obstruction with high sensitivity and specificity and is suitable for use in lung function testing in young children.